FAKTOR YANG MEMENGARUHI TAX AVOIDANCE DENGAN MENGGUNAKAN LEVERAGE SEBAGAI MODERASI - Audrey Da Rosa; Linda Santioso (Jurnal Paradigma Akuntansi, 2026)
This research focuses at how the role of thin capitalization, profitability, and transfer pricing aggressiveness on tax avoidance, and the effect of leverage as a moderating variable on food and beverages sub-sector listed on the Indonesia Stock Exchange (BEI) during 2019-2021. The sample was selected using purposive sampling method with the valid data was 51 samples. Data processing techniques using multiple regression analysis was helped by SPSS program version 29 for windows. The results of this study indicate that the aggressiveness of transfer pricing has a significant negative effect on tax avoidance, while thin capitalization and profitability do not have a significant effect on tax avoidance. Leverage can moderate the relationship between profitability and tax avoidance, but cannot moderate the relationship between thin capitalization and transfer pricing aggressiveness towards tax avoidance. The implication of this research is that the aggressiveness of transfer pricing, increasing profitability ratios, and the high practice of thin capitalization need not worry investors, because these actions do not necessarily indicate tax avoidance by companies.